TRANSFORMASI HUKUM PERUSAHAAN: PENDEKATAN BARU MELALUI BLOCKCHAIN DALAM PENYELESAIAN KASUS KEPAILITAN DI INDONESIA - Selfeny, Risca (Jurnal Hukum Statuta, 2024)
The current corporate legal system in Indonesia still relies on manual and traditional processes for resolving bankruptcy cases. This often results in convoluted, inefficient, and non-transparent procedures. This study aims to explore the potential transformation of corporate law in Indonesia through the application of blockchain technology in bankruptcy case resolution. This research employs normative legal research methods with a juridical-normative approach. Data is collected through literature studies and legislation. The study finds that blockchain technology has the potential to transform corporate law in Indonesia by enhancing efficiency and transparency in bankruptcy case resolution, increasing the security and reliability of data related to bankruptcy cases, and facilitating better collaboration and communication among the various parties involved in the bankruptcy resolution process. The implementation of blockchain technology in resolving bankruptcy cases in Indonesia can provide significant benefits to the involved parties, including debtors, creditors, and judges. Therefore, further studies and concrete efforts are needed to realize the potential transformation of corporate law